Characterization of the VP2 and NS1 genes from canine parvovirus type 2 (CPV-2) and feline panleukopenia virus (FPV) in Northern China - Li, Shaohan; Chen, Xin; Hao, Yunfeng; Zhang, Guangzhi; Lyu, Yanli; Wang, Jianke; Liu, Weiquan; Qin, Tong (Frontiers in Veterinary Science, 2022)
Canine parvovirus (CPV) and Feline panleukopenia virus (FPV) can cause severe diseases in dogs and cats. CPV evolved from FPV, and many CPV variants have been identified via specific amino acid residues. Early studies focused on the capsid protein (VP2); however, there have been limited studies on the non-structural protein (NS1) although it also plays an important role in virus replication, DNA packing, cytotoxicity, and pathogenicity. Eighty-four samples were collected from clinical cases, and CPV-2c was the primary genotype identified in northern China. We also demonstrated both the new CPV-2b strain and CPV-2c strain could infect cats, which indicated that cats can be infected by both FPV and CPV strains. Thirteen codons were identified on the VP2 gene that could be used to distinguish between CPV and FPV. Combined with the relevant research of functional domains, several important mutation sites (at 60, 630, 443, and 545aa) were found in the NS1 gene. The phylogenetic analysis of VP2 and NS1 genes showed certain correlations between geographical regions and genotypes. The gene mutation rates of CPV and FPV have increased in recent years, resulting in a complex pattern of gene evolution in terms of host preference, geographical selection, and new variants. This study provided new insights into the evolution of CPV and FPV, which also reminded us that gene analysis should be based on both structural and nonstructural genes. It also laid the foundation for further study of the epidemiology and molecular evolution of parvoviruses.